THE ROLE OF ARTISTIC TIME AND SPACE IN LITERARY NARRATIVES: A CRITICAL EXPLORATION OF CHRONOTOPES - Sherzod BARATOV; Aigul RAMAZAN; Konyr MUKHATAYEVA; Gulmaria OSPANOVA; Nassiba AKESHOVA (Езиков свят, 2025)
The relevance of the research lies in the fact that artistic time and artistic space are two of the most important literary categories that provide a complete perception of the picture of the world created by the author. This is because not a single work of art can exist in a vacuum. The work examines the theoretical framework and categorization of space and time, emphasizing their application and expression within literary texts. The study extends beyond existing descriptive analyses by critically evaluating the synthesis of space and time as central to narrative construction. The methodological approach combines structural-semantic analysis, comparative evaluation, empirical observation, and conceptual frameworks to provide a comprehensive understanding of these literary categories. This analysis identifies artistic time and space as pivotal elements that transcend their function as narrative tools, asserting their role as dynamic constructs that shape the conceptual and structural integrity of literary works. By exploring the chronotope – a synthesis of these categories – this study advances the understanding of how spatio-temporal dimensions underpin narrative progression and thematic coherence. The spatio-temporal category has several values and a specific purpose, which highlights its unique function in categorising artistic imagery. Time and space, as textual categories, are structured by the mechanisms of interpreting reality, acting as a component of the message and the formation of a literary concept. Lexemes become indicators of conceptually significant information, which allows them to become a substrate of textual meaning. The study concludes that a deeper understanding of content and structure can be achieved by incorporating knowledge of creative time and place, which greatly broadens the scope of literary analysis.